A novel silicon(IV) phthalocyanine-oligopeptide conjugate as a highly efficient photosensitizer for photodynamic antimicrobial therapy. (January 2020) - Zhao, Yang; Ying, Jia-Wen; Sun, Qun; Ke, Mei-Rong; Zheng, Bi-Yuan; Huang, Jian-Dong
Abstract: A novel silicon(IV) phthalocyanine (SiPc) axially di-substituted with Arg-Arg-Arg oligopeptides (compound4 ) has been synthesized and characterized. Meanwhile, two analogues have been used as controls. The effect of arginine number on the spectral properties, photosensitizing activities, partition coefficient, cellular uptake, and photodynamic antimicrobial activities have been investigated. The novel SiPc4 containing tri-arginine oligopeptides exhibits an extremely high in vitro photodynamic activity not only against Gram-positive/negative bacteria but also against fungus, which is obviously superior to its analogues containing mono-arginine (compound2 ) and di-arginine oligopeptides (compound3 ). In addition, 4 shows a higher photodynamic inactivation against S.aureus, E.coli and C. albicans cells than methylene blue (MB), a known antimicrobial photosensitizer. The IC90 values against C. albicans for4 is ca. 179-fold lower than that for MB. Moreover, the potent photodynamic effect of4 has been further confirmed by in vivo animal model. These results indicate that the tri-arginine-modified SiPc is a highly promising photosensitizer for photodynamic antimicrobial therapy. Graphical abstract: Image 1 Highlights: A novel SiPc (4 ) di-substituted with tri-arginine oligopeptides has been prepared. The effect of arginine number between4 and its analogues have been investigated. 4 exhibited a high in vitro photodynamic activity toward both bacteria and fungus cells. 4 showed a highly efficient antimicrobial PDT effect on the in vivo animal model. 4 is a highly promising photosensitizer for photodynamic antimicrobial therapy.